Perancangan Aplikasi Pelayanan Rekam Medis Elektronik Berbasis Smartphone di Rumah Sakit Rafflesia - Saputra, Ripo Andi; Syaputra, Reka Dwi; Harmanto, Deno (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Rafflesia Hospital faces challenges in managing medical records as it still relies on a manual paper-based system. This method can lead to data loss, limited access, and human error, which hinder efficiency and service quality. According to Indonesia’s Ministry of Health Regulation No. 24 of 2022 on Medical Records, all healthcare facilities are required to implement Electronic Medical Records by December 31, 2023. This study aims to design a smartphone-based electronic medical record application for Rafflesia Hospital using the Waterfall development method. The proposed application can improve patient queue management through online registration, provide real-time waiting time information, and enhance communication and coordination among medical teams via a fast information exchange platform. Additionally, the application improves responsiveness and efficiency by granting instant access to critical patient information in emergencies. Clear operational guidelines are established to ensure the application is user-friendly and easy to understand. The hospital needs to prepare for the implementation of this application to integrate it with the Hospital Information System (SIMRS), supporting fast, efficient, and high-quality services.